IMPACT OF LUFFA CYLINDRICAL FIBER ASH ADDITION ON CEMENT PASTE AND CONCRETE CHARACTERISTICS - Dangoma, Kabiru Umar; Tanko, Muhammad; Yusuf, Aminu Bazata; Musa, Aminu Alhaji (FUDMA Journal of Sciences, 2025)
This study investigates the impact of luffa cylindrical fiber ash (LCFA) on behaviour of cement paste and concrete. LCFA was blended with cement from 0 to 10% by its weight, and laboratory tests were carried out to examine the chemical composition of the ash, as well as its physical properties such as standard consistency and setting time. Standard concrete cubes were cast and cured for 7, 14, and 28 days to determine density and compressive strength, following the requirements of BS EN 12390-3. The results of the oxide composition of LCFA revealed that it cannot act as a cement replacement material due to modest SiO₂ content and disproportionately high K₂O level that supports its classification as a low-reactivity and non-pozzolanic biomass ash. Although, the workability results indicated insignificant reduction in slump at high LCFA level, the hardened properties of cement paste and concrete at 28 days curing period, revealed that both density and compressive strength significantly reduced with high LCFA levels; for example, mixes showed reduced compressive strengths from 29.19 to 18.39 MPa. These findings suggest that LCFA lowers the overall performance of concrete when used as additive in cement-based composite. It is therefore more appropriate for non-structural or low-load bearing applications where reduced strength is not a major concern.